Identification and virtual screening of novel salty peptides from hydrolysate of tilapia by-product by batch molecular docking - Ren, Hongjun; Zhou, Jingxuan; Fu, Huixian; Feng, Qiaohui; Wang, Jionghao; Li, Chuan; Xia, Guanghua; Shang, Wenting; He, Yanfu (Frontiers in Nutrition, 2024)
The application of PyRx software enabled batch molecular docking and screening of 16 potential salty peptides from 189 peptides identified in the enzymatic digestion of tilapia by-products. According to sensory analysis, all 16 peptides were predominantly salty with a threshold of 0.256 -0.379 mmol/L with some sourness and astringency, among which HLDDALR had the highest salty intensity, followed by VIEPLDIGDDKVR, FPGIPDHL, and DFKSPDDPSRH. In addition, molecular docking results showed these four core peptides with high salt intensity bound to the salt receptor TRPV1 mainly via van der Waals interactions, hydrogen bonds, and hydrophobic forces; Arg491, Tyr487, VAL441, and Asp708 were the key sites for the binding of salty peptides to TRPV1. Therefore, the application of batch molecular docking using PyRx is effective and economical for the virtual screening of salty peptides.